AB0743 Prevalence of the Metabolic Syndrome According to Various Definitions in Patients with Psoriatic Arthritis. (10th June 2014) - Papagoras, C.; Markatseli, T.E.; Milionis, H.J.; Kaltsonoudis, E.; Voulgari, P.V.; Drosos, A.A.
Abstract : Background: There is evidence that inflammatory joint disease is associated with increased cardiovascular risk. Systemic inflammation and reduced physical activity may be involved through changes in insulin sensitivity and obesity, thus allowing for the emergence of the metabolic syndrome. Objectives: To study the prevalence and components of the metabolic syndrome in patients with psoriatic arthritis (PsA) in comparison with healthy controls. Methods: Non-diabetic patients with PsA followed at a single center and age- and sex- matched healthy controls were included in the study. The metabolic syndrome was defined according to the National Cholesterol Education Program: Adult Treatment Panel III (NCEP:ATP III), the American Heart Association/National Heart, Lung and Blood Institute (AHA/NHLBI), the International Diabetes Federation (IDF) and the Joint Interim Statement (JIS) criteria 1 . Results: Seventy-one PsA patients and 51 healthy controls were included. Patients had significantly lower HDL levels than controls (p<0.001). According to the NCEP:ATP III, AHA/NHLBI, IDF and the JIS criteria respectively, 22.5%, 39.4%, 43.7% and 49.3 of PsA patients had the metabolic syndrome compared to 11.8%, 15.7%, 21.6% and 23.5% of healthy controls (p=0.127 for the NCEP:ATP III, p=0.005 for the AHA/NHLBI, p=0.011 for the IDF and p=0.004 for the JIS criteria). Focusing on the individual metabolic syndrome criteria, PsA patients fulfilled more often the "low HDL" criterion compared to controls (p=0.008). Conclusions: Although the proportion of PsA patients with the metabolic syndrome varies widely by the definition used, it seems that the syndrome is more prevalent in PsA than healthy subjects. Low HDL levels appear to be the main factor driving this difference. References: Circulation. 2009;120:1640-5. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3169